PREVALENCE AND IDENTIFICATION OF GASTROINTESTINAL PROTOZOA IN LONG-TAIL MONKEY IN NUSA PENIDA ISLAND - Putra, Anak Agung Wisnu Kusuma; Wandia, I Nengah; Dwinata, I Made (Buletin Veteriner Udayana, 2020)
This study aims to determine the type and prevalence of protozoa that infects the digestive tract in long-tailed monkeys on the island of Nusa Penida. This study was an observational study, using 50 faces samples taken from 10-15 stools at random locations. Stool was examined using a concentration of flotation method with Zinc Sulphate (ZnSO4) 33.1%. Examination with a 40x microscope objective magnification to look at the morphology. The data obtained are presented descriptively including the type and prevalence of gastrointestinal protozoa in long-tailed monkeys. The study found that there were 40% of gastrointestinal protozoan infections in long-tailed monkeys on Nusa Penida Island. The type of infecting protozoa consists of Entamoeba sp. by 40% and Balantidium coli by 32%. Efforts should be made to prevent the spread of protozoa, through hygiene and sanitation education to the community.